The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00248-013-0253-9
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Profiling and Metagenome Analysis of a Microbial Community from a Habitat Contaminated with Industrial Discharges

Abstract: Industrial units, manufacturing dyes, chemicals, solvents, and xenobiotic compounds, produce liquid and solid wastes, which upon conventional treatment are released in the nearby environment and thus are the major cause of pollution. Soil collected from contaminated Kharicut Canal bank (N 22°57.878'; E 072°38.478'), Ahmedabad, Gujarat, India was used for metagenomic DNA preparation to study the capabilities of intrinsic microbial community in dealing with xenobiotics. Sequencing of metagenomic DNA on the Genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Recent molecular approaches have confirmed most of these old data, and have even shown new important traits of the soil microbiome with respect to the degradation of pollutants. For instance, using metagenomics of microbiomes from industrially-contaminated soil sites in Gujarat (India), Shah et al (2013) identified over 100 different genes for enzymes predicted to be involved in xenobiotic-degradation pathways. Based on these studies, a huge number of potential indicators has become available, however testing of these for robustness regarding the biodegradation potential and activity, and subsequent validation in the context of well-defined soils and metadata, is needed (Shah et al 2013;Sukul et al 2017).…”
Section: Soil Functions That Allow Filtering and Clean-up Of Percolatmentioning
confidence: 99%
“…Recent molecular approaches have confirmed most of these old data, and have even shown new important traits of the soil microbiome with respect to the degradation of pollutants. For instance, using metagenomics of microbiomes from industrially-contaminated soil sites in Gujarat (India), Shah et al (2013) identified over 100 different genes for enzymes predicted to be involved in xenobiotic-degradation pathways. Based on these studies, a huge number of potential indicators has become available, however testing of these for robustness regarding the biodegradation potential and activity, and subsequent validation in the context of well-defined soils and metadata, is needed (Shah et al 2013;Sukul et al 2017).…”
Section: Soil Functions That Allow Filtering and Clean-up Of Percolatmentioning
confidence: 99%
“…For example, it was used for analyzing the microbial communities in uranium tailings and mine water sediment from India [17], revealing the prevalence of biodegradation genes for organic pollutants in activated sludge [18], and assessing the communities of indigenous microorganisms in the contaminated soil with effluents from a variety of industries involved in the manufacturing of various chemicals, dyes, solvents, paints, and other xenobiotic compounds [14]. Kotik et al [19] investigated the bacterial communities in TCE-polluted ground water.…”
Section: Introductionmentioning
confidence: 99%
“…Many xenobiotic-contaminated areas have undergone a shift in microbial community composition [15]. Some bacteria could evolve to utilize a variety of pollutants, whereas a complete degradation of the pollutants depends on the interaction of diverse microorganisms collectively [14], and any individual microorganism is not able to fulfill the degradation of the pollutants completely. As 99% of the environmental microorganisms cannot be cultivated easily [16], metagenome-based analysis of the entire microbial community becomes imperative for delineating the change of microbial community in the contaminated sites with industrial discharges, and for unveiling which metabolic pathway is responsible for biodegradation [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations